Balancing Ethics and Privacy in the Use of Artificial Intelligence in Institutions of Higher Learning: A Framework for Responsive AI Systems - Belinda Ndlovu; Kudakwashe Maguraushe (IJIE (Indonesian Journal of Informatics Education), 2025)
Artificial Intelligence (AI) is swiftly revolutionising higher education, presenting substantial prospects for innovation while concurrently evoking ethical and privacy concerns. These concerns include issues such as intrusive data collection, algorithmic bias, threats to student autonomy, and unequal access to AI-enhanced learning. Without clear guidelines or institutional safeguards, there is a risk that AI systems may reinforce existing social inequalities, compromise student privacy, and erode the human-centred nature of teaching and learning. This research presents an AI framework that is responsive and ethical within the area of higher education. The process involved sixteen in-depth interviews from university students, administrators, lecturers, and IT professionals belonging to three separate universities, with the Technology Organisation Environment model and the sociocultural learning theory being employed. Thematic analysis identified ten critical themes centred around benefits, challenges, applications, responsible use, privacy and data security, ethical considerations, institutional policies and frameworks, training, equity, and sustainable AI use. The results indicate that institutions should take a proactive stance in dealing with these issues and harnessing AI's full potential. The study thus advances the formulation of policies that provide for the equitable distribution of AI technologies, with the accompanying strong emphasis on ethical principles and data security. In preserving academic integrity and enhancing educational processes, this research stresses the need to create collaborative environments among the major stakeholders. Thus, higher education, taking into consideration AI implementations aligned with learner, educator, and administrator interests, thereby offers the promise of navigating the complex terrain of AI integration.